An alternative, arginase-independent pathway for arginine metabolism in Kluyveromyces lactis involves guanidinobutyrase as a key enzyme - Romagnoli, G.; Verhoeven, M. D.; Mans, R.; Rey, Y. Fleury; Bel-Rhlid, R.; Van Den Broek, M.; Seifar, R. Maleki; Ten Pierick, A.; Thompson, M.; Mueller, Volker; Pronk, J. T.; Daran, J. M.; et al. (Molecular Microbiology, 2014)
Most available knowledge on fungal arginine metabolism is derived from studies on Saccharomyces cerevisiae, in which arginine catabolism is initiated by releasing urea via the arginase reaction. Orthologues of the S. cerevisiae genes encoding the first three enzymes in the arginase pathway were cloned from Kluyveromyces lactis and shown to functionally complement the corresponding deletion in S. cerevisiae. Surprisingly, deletion of the single K. lactis arginase gene KlCAR1 did not completely abolish growth on arginine as nitrogen source. Growth rate of the deletion mutant strongly increased during serial transfer in shake-flask cultures. A combination of RNAseq-based transcriptome analysis and 13C-15N-based flux analysis was used to elucidate the arginase-independent pathway. Isotopic 13C15N-enrichment in γ-aminobutyrate revealed succinate as the entry point in the TCA cycle of the alternative pathway. Transcript analysis combined with enzyme activity measurements indicated increased expression in the Klcar1Δ mutant of a guanidinobutyrase (EC.3.5.3.7), a key enzyme in a new pathway for arginine degradation. Expression of the K. lactisKLLA0F27995g (renamed KlGBU1) encoding guanidinobutyrase enabled S. cerevisiae to use guanidinobutyrate as sole nitrogen source and its deletion in K. lactis almost completely abolish growth on this nitrogen source. Phylogenetic analysis suggests that this enzyme activity is widespread in fungi. © 2014 The Authors. Molecular Microbiology published by John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2022-01-11